School Inclusion and Low Vision: An Experience Report (Research, Society and Development, 2020)
This paper aims to present a case study whose object deals with the pedagogical questions of a young person with visual impairment (low vision), 16 (sixteen) years old, enrolled in the 8th grade of Elementary School II and aspects related to perception from the teacher of Specialized Educational Attendance (AEE) and the family about the student's learning processes and school inclusion. We present reflections based on the foundations of Special Education in an inclusive perspective in which we consider ESA an important strategy for promoting the process of school inclusion. In this experience report, the AEE teacher collaborates with the adaptation of activities and assessments and guidance to teachers regarding the strategies to enable student inclusion. The Multifunctional Resource Room provides students with access to software such as Dosvox and other accessible computing resources, tailored activities and the use of concrete materials. As for the family, the mother demonstrates an overprotective posture with regard to stimulating the autonomy and independence of the child. We consider that the school was attentive to the educational needs of the student. However, we realize that the family x school relationship needs strengthening, so that together they can build a systematization of routines and activities that seek to motivate the student to develop their autonomy, aiming at their full development.